Knowledge Extraction from the Language Extended Lexicon Glossary Using Natural Language Processing - Leandro Antonelli; Mario Lezoche; Juliana Delle Ville (TecnoLógicas)
Successful software development requires good specifications, that is, correct, consistent, and unambiguous requirements. Natural language artifacts are the most used tools for writing specifications; nevertheless, the use of natural language can introduce many defects such as ambiguity, vagueness, and generality. In light of this, the purpose of this paper is to propose an approach for writing good specifications and extracting knowledge from them. The proposed approach uses a particular lexicon, the Language Extended Lexicon (LEL) glossary, and suggests rules for extracting knowledge (concepts, attributes, and relationships) from it. This paper also presents a prototype that implements and supports the proposed approach, as well as a preliminary evaluation of the approach. In conclusion, the proposed approach represents a theoretical contribution, which was evaluated using the System Usability Scale, and its evaluation results are promising, as it obtained the maximum score.